The Effect of YouTube Video Media on the Recount Text Writing Ability of Junior High School Students - Kesmi Veronika Simanjuntak; Ezra Saragih; Erick Saut Maruli Sihombing; Daniel Saputra Guring; Dumaris Silalahi (JURNAL PENDIDIKAN BAHASA, 2025)
The low proficiency in writing recount texts among eighth-grade students at SMP Negeri 5 Pematangsiantar is triggered by the dominance of conventional methods, causing students to struggle in developing ideas and reconstructing past experiences. This study aims to examine the effectiveness of using YouTube video media on students' recount text writing ability. This research employed a quantitative approach with a quasi-experimental design. The sample consisted of 62 students divided into an experimental class (VII-2) and a control class (VII-3). Data collection was conducted through writing pre-tests and post-tests, analyzed using the Independent Sample T-Test with SPSS 25. The results showed a significant difference in learning outcomes, where the experimental class achieved a post-test average of 81.33 (Good category), outperforming the control class which only reached 69.56 (Fair category). The statistical test yielded a significance value of 0.000 (p < 0.05), confirming that the alternative hypothesis is accepted. These findings conclude that YouTube video media is effective as a cognitive scaffold in helping students visualize narratives, enrich vocabulary, and organize text structures chronologically.